Occurrence and prognostic relevance of CD30 expression in post-transplant lymphoproliferative disorders. Issue 6 (June 2015) - Vase, Maja Ølholm; Maksten, Eva Futtrup; Bendix, Knud; Hamilton-Dutoit, Stephen; Andersen, Claus; Møller, Michael Boe; Sørensen, Søren Schwartz; Jespersen, Bente; Kampmann, Jan; Søndergård, Esben; Nielsen, Patricia Switten; D'amore, Francesco
Abstract Post-transplant lymphoproliferative disorders (PTLDs) are potentially fatal, often Epstein–Barr virus (EBV)-driven neoplasias developing in immunocompromised hosts. Initial treatment usually consists of a reduction in immunosuppressive therapy and/or rituximab with or without chemotherapy. However, patients who relapse do poorly, and new treatment options are warranted. With the introduction of the immunoconjugate brentuximab vedotin, the CD30 antigen has become an effectively targetable molecule. Therefore, we investigated the frequency and level of CD30 expression in PTLDs. We identified 108 patients with PTLDs diagnosed during 1994–2011, of whom 62 had adequate paraffin-embedded tissue for tissue microarray construction. Immunohistochemical expression of CD30 was consistently detected in all types of PTLD (overall 85.25%), including the monomorphic subtypes, and was correlated with a more favorable outcome. For diffuse large B-cell lymphoma (DLBCL)-type PTLD this was regardless of EBV status, and remained significant in multivariate analysis. Cell-of-origin had no independent prognostic value in our series of DLBCL PTLD.